rammar troublespots : an editing guide for students / Ann Raimes - Raimes, Ann
Grammar Troublespots provides ESL students with a concise volume for avoiding grammar pitfalls in their writing. The text illustrates 21 of the errors most prevalent among students through self-diagnostic flowcharts, explanations, and exercises. In addition, the Second Edition includes new sections on modal verbs and idioms